2016
DOI: 10.1016/j.esd.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and reducing the health and safety impacts of fuel-based lighting

Abstract: The inequity of costly and low-quality fuel-based lighting is compounded by adverse health and safety risks including burns, indoor air pollution, poisoning due to accidental ingestion of kerosene fuel by children, compromised visual health, maternal health issues, and reduced service in health facilities illuminated solely or sporadically with fuel-based lighting. This article compiles and synthesizes information on the health and safety impacts of fuel-based lighting from 135 reports spanning 33 countries. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…found that use of kerosene‐based lighting was associated with a striking 9.43 increased odds of active tuberculosis, highlighting the emerging literature on potential adverse health effects associated with kerosene‐based lighting. Other studies on the use of kerosene either as a cooking fuel or for lighting have focused on acute health impacts such as reduced risk of burns from accidental fire, accidental poisoning from kerosene ingestion, or economic outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that use of kerosene‐based lighting was associated with a striking 9.43 increased odds of active tuberculosis, highlighting the emerging literature on potential adverse health effects associated with kerosene‐based lighting. Other studies on the use of kerosene either as a cooking fuel or for lighting have focused on acute health impacts such as reduced risk of burns from accidental fire, accidental poisoning from kerosene ingestion, or economic outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Other studies on the use of kerosene either as a cooking fuel or for lighting have focused on acute health impacts such as reduced risk of burns from accidental fire, accidental poisoning from kerosene ingestion, or economic outcomes. 16,28 A strength of our study is that it is an epidemiologic study conducted in a large number of residential homes. Another strength is the longitudinal design, which allowed us to adjust for the effect of seasonality on both lighting source and particulate concentrations in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A paired "before-and-after" design was used to assess lamp usage, indoor air quality, and personal exposure before and after the introduction of 3 solar lamps ("baseline" and "follow-up", respectively). A [3][4] week period with the solar lamps separated baseline and followup pollutant measurements in a household. The field work was carried out during January to March 2016.…”
Section: Study Design Overviewmentioning
confidence: 99%
“…Poisoning, burns, and explosions from kerosene are widely recognized problems, but until recently little attention had been paid to potential health impacts of emissions from kerosene combustion . Although there are few epidemiologic studies of the health impacts of residential kerosene use, the existing evidence is strongly suggestive.…”
Section: Introductionmentioning
confidence: 99%
“…Well-documented health risks of kerosene lamps show that exposure to the lamps, which are used indoors and in close proximity to people pose significant health impacts -chronic illness resulting from inhalation of fumes; impairs lung function and increases the risk for respiratory disease, cancer, eye problems, and infectious disease, including tuberculosis, a major health issue in Nigeria (Lam et al, 2012a;Mills, 2014). Inhalation of particulates resulting from indoor combustion causes a range of adverse health effects ranging from tuberculosis to cancer (Dominici et al, 2003;Bai et al, 2007) and asthma (Lam et al, 2012b).…”
mentioning
confidence: 99%